1997
DOI: 10.1021/jp9703263
|View full text |Cite
|
Sign up to set email alerts
|

Long-Range Singlet Energy Transfer in Perylene Bis(phenethylimide) Films

Abstract: The distance over which singlet energy is transferred in polycrystalline films of perylene bis(phenethylimide), PPEI, was measured by a surface quenching technique in films ranging in thickness from 0.04 to 2.3 μm. Radiative energy transfer was not observed. Accurate values of the exciton transfer length could be obtained only with quenchers exhibiting rapid surface quenching velocities (>105 cm/s), such as poly(3-methylthiophene). The measured singlet exciton transfer length of 2.5 ± 0.5 μm is apparently the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
182
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(186 citation statements)
references
References 47 publications
4
182
0
Order By: Relevance
“…By comparing the PL intensity of a polymer film on a planar quenching substrate and a non-quenching substrate for a range of polymer film thickness, the exciton diffusion length (L d ) can be determined. [64][65][66] Glass was used as the non-quenching substrate, while a thin layer of TiO 2 coated on glass with or without IM was the quenching substrate. Thin TiO 2 (~5 -8 nm) was used to ensure a negligible effect from optical interference.…”
Section: Models For Increased Photocurrent Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…By comparing the PL intensity of a polymer film on a planar quenching substrate and a non-quenching substrate for a range of polymer film thickness, the exciton diffusion length (L d ) can be determined. [64][65][66] Glass was used as the non-quenching substrate, while a thin layer of TiO 2 coated on glass with or without IM was the quenching substrate. Thin TiO 2 (~5 -8 nm) was used to ensure a negligible effect from optical interference.…”
Section: Models For Increased Photocurrent Yieldmentioning
confidence: 99%
“…When deposited on bare TiO 2 or -NH 2 modified TiO 2 , P3HT exhibits some quenching at large thickness, but the quenching never approaches 100% as its thickness is reduced. 64 This lack of complete quenching is unexpected because in very thin film of polymers (d < L d ), all the excitons should be able to diffuse to the quenching interface. For thin films where the absorption is assumed to be linear with thickness, the quenching profile follows:…”
Section: Models For Increased Photocurrent Yieldmentioning
confidence: 99%
“…The development of accurate measurements of the exciton diffusion length is therefore important for organic photovoltaics and the optimisation of materials, processing and device structure. To date there has been a wide range of reported values for different materials obtained by techniques such as surface quenching, [5][6][7][8] volume quenching, [9,10] microwave conductivity, [11] exciton-exciton annihilation [12,13] and photocurrent modelling of solar cells. [14] Of these the surface quenching technique is probably the most used, where the organic material is deposited onto a suitable quencher, resulting in a loss of luminescence.…”
mentioning
confidence: 99%
“…[9] Recent studies have shown BPE-PTCDI to be an excellent n-channel organic semiconductor, possessing both a high n-type mobility (≈ 0.1 cm 2 V -1 s -1 ) and good stability in air over several weeks. [11] A remarkably long exciton diffusion length of 2.3 lm was estimated [12] for solvent-annealed, evaporated thin films of this material, making it an attractive candidate for use in bilayer device structures. Its HOMO level was measured to be -6.1 eV by ultraviolet photoelectron spectroscopy (IPES) [13] indicating that it is a strong acceptor with respect to CuPc (HOMO = -5.0 eV).…”
mentioning
confidence: 99%